2017
DOI: 10.4103/wjnm.wjnm_31_17
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on the accuracy of positron emission tomography/computed tomography and positron emission tomography/magnetic resonance imaging in the management of ovarian cancer: Is functional information really needed?

Abstract: Ovarian cancer (OC) often presents at an advanced stage with frequent relapses despite optimal treatment; thus, accurate staging and restaging are required for improving treatment outcomes and prognostication. Conventionally, staging of OC is performed using contrast-enhanced computed tomography (CT). Nevertheless, recent advances in the field of hybrid imaging have made positron emission tomography/CT (PET/CT) and PET/magnetic resonance imaging (PET/MRI) as emerging potential noninvasive imaging tools for imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 68 publications
1
18
1
Order By: Relevance
“…Conventional imaging techniques are not considered sufficiently adequate to assess LN involvement in AOC . Functional imaging techniques such as positron emission tomography/computed tomography and diffusion‐weighted magnetic resonance imaging seem to be the most accurate techniques for predicting the pathological status of retroperitoneal LNs in OC …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional imaging techniques are not considered sufficiently adequate to assess LN involvement in AOC . Functional imaging techniques such as positron emission tomography/computed tomography and diffusion‐weighted magnetic resonance imaging seem to be the most accurate techniques for predicting the pathological status of retroperitoneal LNs in OC …”
Section: Discussionmentioning
confidence: 99%
“…22,23 Functional imaging techniques such as positron emission tomography/computed tomography and diffusion-weighted magnetic resonance imaging seem to be the most accurate techniques for predicting the pathological status of retroperitoneal LNs in OC. [23][24][25] Currently, no intraoperative imaging technique exists that can be used to accurately detect involved LNs either intraoperatively, by guiding lymphadenectomy, or after lymphadenectomy (ex vivo), guiding the pathologist for operative specimen analysis. 23 FI using IV injection of ICG has been reported to be a new promising noninvasive technology for the detection of metastatic tumor cell deposits in LNs of head and neck cancer, hepatocellular carcinoma, colorectal cancer, and prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sophisticated sequences such as diffusion-weighted imaging, functional MRI, and MR spectroscopy can all be incorporated with molecular imaging, giving further information but with less radiation exposure. This can provide a significant reduction in radiation dose and exposure in patients who require follow-up imaging [3].…”
Section: Other Research-based Imaging Techniques and Work In Progressmentioning
confidence: 99%
“…This chapter regarding diagnostic imaging aims to guide multidisciplinary teams to decide on further investigation of ovarian cancer (OC), by proposing a diagnostic imaging algorithm (Figure 1) for the detection and staging of this disease [1,2]. Furthermore, it provides a special focus on the evolving utility of molecular imaging, specifically PET/CT imaging in the management of ovarian cancer [3].…”
Section: Introductionmentioning
confidence: 99%
“…The use of functional imaging in clinical practice, such as technetium99mhexamethylpropylene amine oxime SPECT and 18F-FDG positron emission tomography/computed tomography (PET/CT), as well as amyloid imaging PET/CT, is gaining momentum as noninvasive imaging biomarkers to provide a better diagnostic accuracy. [8][9][10] Molecular imaging using 18F-FDG PET/CT has been widely used for oncology imaging, 8,11 and also for diagnosing infection,12 neurology, and cardiology cases.13 Previous research has shown that 18F-FDG PET/CT can act as a noninvasive biomarker of cognitive decline and this imaging technique is widely available in several centers.14 Measurement of cerebral glucose hypometabolism acts as a surrogate biomarker for NCDs, wherein reduced activity in the temporoparietal lobes of the brain is a hallmark of Alzheimer's disease. 15 The quantitative measurement for PET/CT uses standardized uptake values (SUVs) that take into account the ratio of FDG distribution in the body.…”
mentioning
confidence: 99%